IMPLEMENTASI MATAKULIAH MANAJEMEN SUMBEDAYA KELUARGA DAN MASYARAKAT TERHADAP PENGELOLAAN SUMBERDAYA KEUANGAN PADA MAHASISWA AKS-AKK YOGYAKARTA - Prihatin Saraswati (Jurnal Socia Akademika, 2022)
This study aims to see the relationship between student knowledge in the Family and Community Resource Management course to its implementation in student financial management. This research uses quantitative methods with survey techniques on respondents of AKS-AKK students who take the Family and Community Resource Management course. The purposive sampling method of 30 students. Data retrieval using questionnaires. The results of the study obtained that the implementation of the Family and Community Resource Management course in financial management, students showed that respondents had understood enough to make financial planning, implementation, and evaluation, especially personal finances